Czynniki kształtujące strukturę agrarną i działalność rolniczą w regionie północno-zachodnim - Wawrzyniak, Bogdan M.; Wojtasik, Bolesław (Factors Shaping Agrarian Structure and Farming Activities in North-West Region, 2005)
The aim of the paper is to analyse five north-west provinces on the background of the country as regards to agrarian structure and farming activities.The agrarian structure is analysed as regards to arable lands area.Characterizing farming activities shrinking the number of farms running this activity is stated. The main motives of giving up production are economic, healthy and family ones.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 394-399